Sepsis, Coagulation, and Antithrombin: Old Lessons and New Insights - Levi, Marcel; Schouten, Marcel; van der Poll, Tom (Seminars in thrombosis and hemostasis, 2008)
ABSTRACT Current insights in the pathogenesis of multiple organ dysfunction in patients with sepsis point to a pivotal role of inflammation and coagulation. One of the most important mechanisms contributing to the activation of coagulation in sepsis is the downregulation of physiologic anticoagulant systems, such as the antithrombin pathway. More than 20 years ago, Eberhard Mammen already hypothesized that coagulation activation and antithrombin were important factors in patients with sepsis. Abundant experimental and clinical studies have supported that notion in recent years. The better understanding of the pathogenesis of coagulation activation and the role of natural anticoagulants in sepsis has led to the development of anticoagulant factor concentrates, such as antithrombin concentrate. Clinical studies indicate that these interventions may have a role in the (supportive) treatment of patients with sepsis, mostly based on surrogate outcomes, but ongoing studies will have to confirm a beneficial effect in reducing mortality.